INVESTIGATION ON THE PROPERTIES OF PEDUNCULATE OAK WOOD AFFECTED BY OAK DECLINE - Dumitru LICA; Camelia COŞEREANU (Pro Ligno, 2014)
The combination of damaging agents, as biotic and abiotic factors, has as effect the deterioration in the appearance of the foliage of affected trees and then, progressive death of branches. Large numbers of pedunculate oak (Quercus robur) and sessile oak (Quercus petraea) trees are declining in the Central Romania. Depending on the deterioration of the foliage and of the branches, five grades of infestation levels of oak trees were determined. The objective of this study was to investigate the quality of wood obtained from those infested trees by analysing the cellulose and lignin content, physical properties such as moisture content, density, shrinkage from fibre saturation moisture content, permeability of wood to water, and mechanical properties, such as MOE, MOR for static stresses, tensile strength perpendicular to the grains, shearing strength and Janka hardness perpendicular to the grains. The more representative samples of trees affected by oak decline for the five grades of infestation levels of trees were randomly selected and harvested. They were cut into logs and then sampled for the chemical, physical and mechanical testing. The results of this study showed that the poor quality of wood resulted from the logs affected by oak decline at the final stage (five grade of infestation level) could not be used for furniture and other wooden products manufacturing.